Association Between Chronic Periodontal Disease and Erectile Dysfunction: A Case–Control Study. Issue 2 (March 2022) - Huang, Nannan; Li, Chanxiu; Sun, Wenjuan; Yang, Yuhong; Tang, Qian; Xiao, Feng
Erectile dysfunction (ED) and chronic periodontal disease (CPD) share mutual risk factors, and the incidence of ED is increasing among young adults. The relation of CPD and ED remains obscure due to inconsistent clinical evidence. This study aimed to further assess the relationship between CPD and ED using the Community Periodontal Index of Treatment Need (CPITN) and the International Index of Erectile Function (IIEF). Totally, 202 adult men were included, with 100 subjects with ED in the case group and 102 subjects without ED undergoing routine dental examinations in the control group. The IIEF questionnaire was used to assess the severity of ED, and CPD was assessed through the Community Periodontal Index (CPI) score. Periodontal assessments were performed by one single calibrated examiner. Logistic regression analysis was performed for the association between CPD and ED. After adjustment for age, smoking status, tooth brushing time, education level, monthly income, tooth brushing frequency, and gum bleeding, higher CPI score was identified to be associated with a greater risk of ED (odds ratio [OR] = 2.755, 95% confidence interval [CI] = [1.400, 5.423], p = .003), suggesting that CPD was positively associated with the odds of ED. CPD was getting more severe with the progress of ED ( p < .05). Men with ED could be encouraged to receive routine dental examinations and appropriate preventive dental measures to maintain oral and periodontal health.